Functional and clinical outcome of arthroscopic versus mini-open bankart repair in anterior shoulder instability - Ismail Mansor, Nur Akmal; Che Ahmad, Aminudin; Hamdan, Amiruddin; Nik Mohd Najmi, Nik Mohd Fatmy (Malaysian Orthopaedic Association (MOA), 2017)
INTRODUCTION: The shoulder is the most common major joint to dislocate, accounting for 45% of all dislocation. The gold standard for the treatment of anterior shoulder instability was open bankart repair. However, the trend has shifted to arthroscopic repair. This study was designed to evaluate and compare the functional and clinical outcome of Arthroscopic and Mini-open Bankart repair method.